Comprehensive study of recycling of thermosetting polymer composites – Driving force, challenges and methods. (15th February 2021) - Utekar, Shubham; V K, Suriya; More, Neha; Rao, Adarsh
Abstract: The thermosetting polymer composites are considered to be a revolutionary material due to their superior properties and versatility in application. The growth extent in the manufacturing and rigorous usage of polymer composites raised the environmental concerns due to the disposal constraints. This article discusses the various methods used for recycling the thermosetting polymer composites. The term "recycling" has been stressed in most of the engineering applications since civilization. This article explains the potential methods by which the materials or the energy can be recovered through the recycling process. The authors have also tried to comprehend the need for recycling and the early approaches made. This review has been developed with few suggestions on advanced methods and their scope in the recycling of thermoset composites.